Simulation of Three-Phase Induction Motor Control Using Fuzzy Logic Controller - Omar Said, Algayash Bennanes (2004)
A fuzzy logic controller has been developed and simulated on an indirect vector control of an induction motor (IVCIM) drive system. The objective of the indirect vector control is to convert the three-phase induction motor into a linear device where the torque and the flux in the motor can be controlled independently. The induction motor is fed by a current-controlled PWM inverter. The proposed fuzzy speed controller block in a vector controlled drive system observes the pattern of the speed loop error signal and correspondingly updates its output, so that the actual speed matches the command speed. The design of the fuzzy controller starts with identifying the inputs, performing the membership functions for the two inputs of the FLC and ends at manipulating the final command signal to the current regulator which triggers the inverter.The fuzzy logic toolbox has been used to build the fuzzy inference system (FIS) which is the dynamo of the fuzzy logic controller. The proposed FLC controller has been designed to meet the speed tracking requirements under a step change in speed and load changes. The proposed FLC drive dynamic performance has been investigated and tested under different operating conditions by simulation in the SimulinMMatlab software environment. In order to prove the superiority of the FLC, a conventional PI controller based IM drive system has also been simulated. The simulation results obtained have proved the very good performance and robustness of the proposed FLC. It is concluded that the proposed fuzzy logic controller has shown superior performances over the conventional PI controller.